English language communicative competence of university interns for employability - Manjet Kaur Mehar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study discusses English Language Communicative Competence (ELCC) of university interns during their eight-week internship. The aim of the study is to identify the importance of workplace oral and written communicative tasks from the lens of university interns. Quantitative methodology using an adopted questionnaire was employed among sixty-eight participants selected purposively. The instrument examined the university interns’ written and oral language skills in internal and external workplace communication. It also examined the adequacy of university’s preparation for the future graduates to manoeuvre their ELCC ability at workplace. Findings obtained from university interns revealed high frequency engagement with written and oral communicative tasks in internal and external workplace contexts in terms of emails, team-based discussion, telephone communication and general workplace writing. Further, tasks such as handling the writing of proposals, manuals and business letters were found to be challenging. The findings also revealed inadequacy of university’s training in equipping future graduates with ELCC for improved graduate employability. The issues highlighted require attention of higher education providers to enhance university interns’ ELCC. In addition, collaborative input from the industry is also highly encouraged to improve ELCC training of university interns for future employment.